Concepts of Crime and Criminology (International Journal of Innovative Research in Engineering & Management, 2021)
By delving deeply into the core mind set or state of mind of the  individual committing crime, the notion of crime and  criminology may be grasped. This article also discusses the  motives for the crime and the variables that influence a person's  decision to commit a crime. It also covers the idea of crimes  and the different regulations that have been established for the  commission of certain offenses. This page also covers a variety  of criminology ideas that have been classified according to the  MENS REA that led to the crime. Apart from that, this article  also discusses the many sorts of offenses that have been  recognized by the law. What is crime, in its most basic form?  What are the elements that lead to criminal activity? What are  the various punishments that have been established for various  crimes? What are the several courts that have jurisdiction over  criminal cases? What special criminal provisions have been  established in the jurisdiction? All of these debates have been  covered in this article. This article also covers the fundamentals  of criminology and the different components that contribute to the definition of the term. The idea of criminology has been  separated into two sections in this article: one half discusses the  reasons that lead to a victim being a victim, and the other  portion discusses the variables that lead to a person becoming  an offender. Aside from crime and criminology, this article  discusses the different responsibilities and capabilities of  criminal courts, which are critical in establishing what  constitutes a crime and dealing with criminal cases.
Keywords: Actus Rea; Crimen; Crime; Mens Rea; Violence